4 Improving Undergraduate and Postgraduate Medical Trainees Confidence and Competence in Electrocardiogram Interpretation. (31st May 2014) - Gill, Simrat; McAloon, Christopher; Leach, Helen; Trevelyan, Jasper
Abstract : Introduction: The Electrocardiogram (ECG) is the most commonly used diagnostic test in modern medicine. 1 Competency in ECG interpretation is central to undergraduate and postgraduate clinical training and minimising potential adverse consequences on patient care. Several studies have demonstrated postgraduates interpret ECG's sub-optimally. 2, 3 Our study compares the effectiveness of two cost neutral learning strategies to improve competence and confidence in this core clinical skill. Method: A prospective randomised study was carried out over a one-month period comparing the learning strategies in two cohorts: undergraduate 3 rd year medical students and postgraduate foundation year one (FY1) doctors.Both had blinded randomisation to one of these strategies; focused teaching program (FTP) and self-directed learning (SDL). All volunteers completed a confidence questionnaire on ECG interpretation before and after completing the intervention. Additionally, all undertook an ECG recognition multiple choice question (MCQ) paper at the end of the learning period to assess competence. Results: A total of 21 FY1's and 25 3rd year medical students participated. The undergraduates in the FTP group demonstrated a significant difference in successfully interpreting 'Ventricular Tachycardia' (p = 0.046) and 'Narrow Complex Tachycardia' (p = 0.009) than the SDL group. Overall, participant confidence increased in both groups in each cohort. The FTP group demonstrated a greater improvement in confidence compared to SDL in both cohorts. Conclusion: A dedicated teaching program can improve trainee confidence and competence in ECG interpretation. A larger benefit is observed in those undertaking a focused teaching program. ECG interpretation can be improved at any training level, especially undergraduates with a dedicated teaching program. References: Rubinstein J, Dhole A, Ferenchick G. Puzzle based teaching versus traditional instruction in electrocardiogram interpretation for medical students – a pilot study. BMC Medical Education 2009; 9(4):1–7 Sur D, Kaye L, Mikus M, Goad J, Morena A. Accuracy of electrocardiogram reading by family practice residents. Fam Med 2000; 32(5): 315–9 Jensen MSA, Thomasen JL, Jensen SE, Lauritzen T, Engberg M. Electrocardiogram interpretation in general practice. Family Practice 2005; 22:109–113